Phytochemicals from Camellia nitidissima Chi inhibited the formation of advanced glycation end-products by scavenging methylglyoxal. (15th August 2016) - Wang, Weixin; Liu, Haiyan; Wang, Zhennan; Qi, Jing; Yuan, Shengtao; Zhang, Weijie; Chen, Hongjuan; Finley, John W.; Gu, Liwei; Jia, Ai-Qun
Highlights: The total phenolic and quercetin content in ethanolic extract and different fractions were studied. 16 phenolic compounds were identified using HPLC/HRMS method. The dichloromethane and ethyl acetate fraction possessed better effects of inhibiting AGE formation. Both mono- and di-methylglyoxal quercetin adducts were detected using HPLC–ESI-MS n . Abstract: The objective of this study was to investigate the inhibitory effects of Camellia nitidissima Chi (CNC) on the advanced glycation end-product (AGE) formation. CNC was extracted with ethanol and further separated into dichloromethane, ethyl acetate, n -butanol, and water soluble fractions. Ethyl acetate fraction had the highest total phenolic and quercetin content compared with other fractions. Sixteen phenolic compounds were identified using HPLC Triple TOF MS/MS. Bovine serum albumin (BSA)–glucose assay showed that dichloromethane and ethyl acetate fraction inhibited AGE formation by 88.1% and 87.5% at 2.5 mg/mL. BSA–methylglyoxal assay showed that ethyl acetate fraction inhibited 54.1% AGE formation while dichloromethane fraction inhibited 28.1%. Over 96.0% of methylglyoxal was scavenged by different fractions within 12 h. Both mono- and di-methylglyoxal quercetin adducts were identified after incubating quercetin with methylglyoxal using HPLC–ESI-MS n . The results in this study suggest that CNC extracts inhibited AGEs formation in part through scavenging methylglyoxal by phenolic compounds.